2018
DOI: 10.1016/j.psychres.2017.11.068
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of remission from PTSD symptoms after sexual and non-sexual trauma in the community: A mediated survival-analytic approach

Abstract: Epidemiological data on the chronicity of posttraumatic stress disorder (PTSD) symptoms in relation to trauma type and underlying pathways are rare. The current study explored how PTSD symptoms change over time across different trauma types and examined mediators of their persistence. A trauma-exposed community sample, whereof approximately one quarter met diagnostic criteria for PTSD, provided retrospective data on the duration of PTSD symptoms. Those who remitted and those who had not at the time of assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 63 publications
(78 reference statements)
3
17
0
Order By: Relevance
“…With Hubei being the epi-affected area at that time, it is understandable that local residents may have had more severe traumatic experiences, leading to more severe PTSS. Many previous studies also indicated that the severity of trauma was an important predictor of PTSS ( 45 , 46 ). In model 2, the main effects of being currently in Hubei and a high-risk public were significant.…”
Section: Discussionmentioning
confidence: 82%
“…With Hubei being the epi-affected area at that time, it is understandable that local residents may have had more severe traumatic experiences, leading to more severe PTSS. Many previous studies also indicated that the severity of trauma was an important predictor of PTSS ( 45 , 46 ). In model 2, the main effects of being currently in Hubei and a high-risk public were significant.…”
Section: Discussionmentioning
confidence: 82%
“…Previous survival methods were conducted in PTSD populations mostly using single sampling and only demographic and clinical variables. For example, Müller et al. (2018) implemented a survival analytic approach from a lifetime perspective, to determine whether the expected duration of time until PTSD remission was related to a specific type of trauma, and to identify mediators of PTSD remission or persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kelley et al and Smith et al showed that PTSD following a sexual trauma was associated with a higher symptom severity 7,20 . On the other hand, Müller et al concluded that remission took more time and effort in PTSD patients with a history of sexual trauma 23 . In Turkey, the study by Çoban et al also shows that PTSD related to sexual trauma displayed more severe symptoms 10 .…”
Section: Discussionmentioning
confidence: 99%